Teacher’s Use of Code Switching in the Classroom and Its Implications on Students’ Score - Clara Herlina K. (Bina Nusantara University, 2007)
Code switching is usually done by people who have mastered two languages well. Among the people who can fulfill these criteria are Indonesians who teach English. In teaching English to Indonesian students, English teachers do not always use English as the medium of instruction, they usually code switch to Indonesian. Research focuses on the teachers as the subjects who apply code switching in the classroom. The respondents are eight lecturers in Bina Nusantara University who teach English to non-English department students. This research analyses the speech of the teachers to find out the percentage of code switching and the uses of code switching in the classroom. Finally, the relation between code switching and the students’ scores is calculated using independent samples T-test.